2016
DOI: 10.1111/ele.12594
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of pollinator‐mediated interactions using pollen transfer networks: evidence of widespread facilitation in south Andean plant communities

Abstract: Information about the relative importance of competitive or facilitative pollinator-mediated interactions in a multi-species context is limited. We studied interspecific pollen transfer (IPT) networks to evaluate quantity and quality effects of pollinator sharing among plant species on three high-Andean communities at 1600, 1800 and 2000 m a.s.l. To estimate the sign of the effects (positive, neutral or negative), the relation between conspecific and heterospecific pollen deposited on stigmas was analysed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
155
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(168 citation statements)
references
References 79 publications
(189 reference statements)
4
155
2
1
Order By: Relevance
“…Although the identity of the heterospecific neighbour can determine the outcome of plant-plant interactions (Arceo-G omez et al 2019), overall heterospecific density was shown to affect the pollination of a single species (Albor et al 2019). The prevalence of interspecific facilitation is expected when pollinators are scarce (Rathcke 1983), which was demonstrated experimentally (L azaro et al 2014) and in pollinator-depauperate communities (Tur et al 2016). In these communities, plant species are under scarce pollination environments and, thus, jointly benefit from increases in pollinator attraction.…”
Section: Discussionmentioning
confidence: 99%
“…Although the identity of the heterospecific neighbour can determine the outcome of plant-plant interactions (Arceo-G omez et al 2019), overall heterospecific density was shown to affect the pollination of a single species (Albor et al 2019). The prevalence of interspecific facilitation is expected when pollinators are scarce (Rathcke 1983), which was demonstrated experimentally (L azaro et al 2014) and in pollinator-depauperate communities (Tur et al 2016). In these communities, plant species are under scarce pollination environments and, thus, jointly benefit from increases in pollinator attraction.…”
Section: Discussionmentioning
confidence: 99%
“…Data from flowering plant communities in the Andes suggest that pollinator‐mediated facilitation can be even more common than competition in some ecosystems (Tur et al . ). Similarly, Hegland et al .…”
Section: Introductionmentioning
confidence: 97%
“…Facilitation is well known among plants (Johnson et al 2003;Moeller 2004). Data from flowering plant communities in the Andes suggest that pollinator-mediated facilitation can be even more common than competition in some ecosystems (Tur et al 2016). Similarly, Hegland et al (2009) reported mainly facilitative interactions via pollinator attraction among six plant species in a temperate grassland community.…”
Section: Introductionmentioning
confidence: 98%
“…This could be because alpine species possess compensatory traits that allow them to deal with pollinator scarcity thereby decreasing pollen limitation [2730]. One such trait is potential flower longevity, the time a flower is able to remain open be and available to be pollinated.…”
Section: Introductionmentioning
confidence: 99%